δ60Ni and δ13C Composition of Serpentinites and Carbonates of the Tekirova Ophiolite, Turkey, and Meatiq Ophiolite, Egypt - Neubeck, Anna; Boosman, Arjen; Hosgörmez, Hakan; Özcan, Dogacan; Boskabadi, Arman; Ivarsson, Magnus; Rouxel, Olivier (Frontiers in Earth Science, 2021)
Nickel isotope fractionation patterns in continental ultramafic environments generally show a depletion of δ60Ni in weathered rocks and an enrichment in bedrock samples. The present study focuses on stable Ni isotope fractionation patterns in carbonate-rich, ultramafic ophiolite samples with concomitant fluids at an active serpentinization site in southwestern Turkey, with a comparison to results from an inactive serpentinization site in the Eastern Desert of Egypt with carbonate-rich samples. All solid phase data from the inactive serpentinization area are consistent with previously reported values from serpentinites, whereas the solid precipitates in the active area (SW Turkey) give values slightly heavier than previously reported data. However, the Ni isotopic signatures in the active serpentinization system likely reflect the scavenging of light Ni by iron oxide and carbonate precipitation, as has been previously demonstrated in laboratory coprecipitation experiments. It is also possible that the active system results resemble previous laboratory experimental results that show a relatively strong initial fractionation between fluids and liquids, which then diminishes with time due to aging of the precipitates.